Dependence and Uniqueness in Bayesian Games. - Beggs, A (Department of Economics (University of Oxford), 2012)
This paper studies uniqueness of equilibrium in symmetric 2 x 2 bayesian games. It shows that if signals are highly but not perfectly dependent then players play their risk-dominant actions for all but a vanishing set of signal realizations. In contrast to the global games literature, noise is not assumed to be additive. Dependence is modeled using the theory of copulas.